NOS LABIRINTOS DE UMA GEOGRAFIA ANTI-HISTÓRICA TRUMAN, O SHOW DA VIDA - Martins, Sérgio (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2007)
Based on the movie The Truman Show, the author discusses the relation between the (re)production of space and everyday life, searching to explain the (im)possibilities of creation in an apparently closed time-space totality.